2020
DOI: 10.1038/s41598-020-58549-8
|View full text |Cite
|
Sign up to set email alerts
|

From physical to social interactions: The relative entropy model

Abstract: complex social systems at various scales of analysis (e.g. dyads, families, tribes, etc.) are formed and maintained through verbal interactions. Therefore, the ability to (1) model these interactions and (2) to use models of interaction for identifying significant relations may be of interest to the social sciences. Adopting the perspective of social physics, we present a general approach for modeling interactions through relative entropy. For illustrating the benefits of the approach, we derive measures of "p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Real Madrid's unpredictability in passing may have increased the chances of goal-scoring opportunities, potentially having contributed to the win. The concept of entropy to model social interactions has already been used [26][27][28]. Newman and Vilenchik (2019) used the concept of relative entropy to model the interactions of players passing the ball in football, having found that when comparing two opposing teams, higher entropy values lead to more chances of creating goal-scoring opportunities [27].…”
Section: A Case Studymentioning
confidence: 99%
“…Real Madrid's unpredictability in passing may have increased the chances of goal-scoring opportunities, potentially having contributed to the win. The concept of entropy to model social interactions has already been used [26][27][28]. Newman and Vilenchik (2019) used the concept of relative entropy to model the interactions of players passing the ball in football, having found that when comparing two opposing teams, higher entropy values lead to more chances of creating goal-scoring opportunities [27].…”
Section: A Case Studymentioning
confidence: 99%
“…The application of the concept of entropy to model the interactions of players passing the ball in football has also been used [16][17][18], pointing to higher entropy values leading to greater chances of creating goal-scoring opportunities [17]. The importance of entropy in football lies in the recognition that variability in the behavioral patterns of interaction between players is beneficial for the team, as the system is more unpredictable.…”
Section: Introductionmentioning
confidence: 99%